Durian Fruits Discovered as Superior Folate Sources - Striegel, Lisa; Chebib, Soraya; Dumler, Caroline; Lu, Yuyun; Huang, Dejian; Rychlik, Michael (Frontiers in Nutrition, 2018)
Durian (Durio zibethinus) is a tropical fruit grown in Southeast Asia and highly appreciated by consumers throughout Asia. Folates are a group of vitamins and are essential nutrients for humans. Here we present the folate analysis of different durian cultivars as well as diverse durian products. An LC-MS/MS method and the application of a stable isotope dilution assay was used for quantitation of the folate vitamers 5-methyltetrahydrofolate, 5-formyltetrahydrofolate, 10-formylfolate, tetrahydrofolate and pteroylmonoglutamic acid by using [13C5]-labeled internal standards. Total folates varied from 175 to 440 µg/100 g for durian arils and from 15.0 to 417 µg/100 g for durian products. These contents are extraordinarily high compared to other fruits and may be correlated to the upregulated methionine biosynthesis pathway reported recently. In summary, the tropical fruit durian can be considered as a very rich dietary source of natural folates.